2020
DOI: 10.1111/jopr.13259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intaglio Surface Adjustment in the Oral Cavity for Lithium Disilicate Crowns Fabricated Using Different Scanners

Abstract: Purpose A clinical study to evaluate the intraoral adjustment of crowns fabricated using different scanners. Materials and Methods A total of 15 patients requiring single ceramic crowns were recruited. Impressions were made according to four protocols: a conventional approach and using three intraoral scanners (IOSs) (CS3600 (Carestream Dental, Atlanta, GA), i500 (Medit, Seoul, Republic of Korea), and EZIS PO (DDS, Seoul, Republic of Korea)). Four crowns per patient were fabricated using lithium disilicate cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Scan accuracy for fixed dental prostheses has been assessed. [10][11][12][13][14] From a clinical study, Lee et al 13 reported that IOSs influence the marginal and internal fit of fixed dental prostheses. Moreover, clinically acceptable scan accuracy to within 100 mm for fixed dental prostheses has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Scan accuracy for fixed dental prostheses has been assessed. [10][11][12][13][14] From a clinical study, Lee et al 13 reported that IOSs influence the marginal and internal fit of fixed dental prostheses. Moreover, clinically acceptable scan accuracy to within 100 mm for fixed dental prostheses has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 20 evaluated the intaglio surface trueness of zirconia crowns fabricated with 3D printing and verified the volumetric stability of the fabricated zirconia crowns. In a previous clinical study, virtual models of crowns before and after intraoral adjustment were superimposed to assess intaglio surface trueness, and the intraoral adjustment of crowns was verified 21 . In this study, to evaluate the effect of the four finish line locations, crowns fabricated in four finish line locations and crowns designed in a reference tooth preparation were superimposed and the intaglio surface trueness was evaluated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated 3D trueness to verify the dimensional change of the intaglio surface of the fabricated dental prosthesis 17 19 . Previous studies can be different depending on what is designated as a reference model, such as the manufacturing precision of 3D printers 20 and the adjustment of the intaglio surface of the crown in the oral cavity 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [20] evaluated the intaglio surface trueness of zirconia crowns fabricated with 3D printing and veri ed the volumetric stability of the fabricated zirconia crowns. In a previous clinical study, virtual models of crowns before and after intraoral adjustment were superimposed to assess intaglio surface trueness, and the intraoral adjustment of crowns was veri ed [21]. In this study, to evaluate the effect of the four nish line locations, crowns fabricated in four nish line locations and crowns designed in a reference tooth preparation were superimposed and the intaglio surface trueness was evaluated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated 3D trueness to verify the dimensional change of the intaglio surface of the fabricated dental prosthesis [17][18][19]. Previous studies can be different depending on what is designated as a reference model, such as the manufacturing precision of 3D printers [20] and the adjustment of the intaglio surface of the crown in the oral cavity [21].…”
Section: Introductionmentioning
confidence: 99%